3(-5a+9)-2(4a+6)=

Simple and best practice solution for 3(-5a+9)-2(4a+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-5a+9)-2(4a+6)= equation:


Simplifying
3(-5a + 9) + -2(4a + 6) = 0

Reorder the terms:
3(9 + -5a) + -2(4a + 6) = 0
(9 * 3 + -5a * 3) + -2(4a + 6) = 0
(27 + -15a) + -2(4a + 6) = 0

Reorder the terms:
27 + -15a + -2(6 + 4a) = 0
27 + -15a + (6 * -2 + 4a * -2) = 0
27 + -15a + (-12 + -8a) = 0

Reorder the terms:
27 + -12 + -15a + -8a = 0

Combine like terms: 27 + -12 = 15
15 + -15a + -8a = 0

Combine like terms: -15a + -8a = -23a
15 + -23a = 0

Solving
15 + -23a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -23a = 0 + -15

Combine like terms: 15 + -15 = 0
0 + -23a = 0 + -15
-23a = 0 + -15

Combine like terms: 0 + -15 = -15
-23a = -15

Divide each side by '-23'.
a = 0.652173913

Simplifying
a = 0.652173913

See similar equations:

| 5.25(2)+3.25=10.25+1.75(2) | | 6x^3-12x^2+10x-20=0 | | -10w+2=2w+18 | | 13x+11=12x+3 | | 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 | | -5x+12=-5x+-12 | | 16Y-7y=500 | | 4x-3+0=-3x-4 | | ((12k^2h)-(3kh^2))/3kh | | 0.25(8-4p)+2p=12 | | 2x+19y=300 | | 60=x+71 | | -3(6-8n)=-138 | | 35-6x=13+5x | | 5(x-2)-8x=-16 | | 8-15=3/7b | | (x)(30-2x)(16-2x)=0 | | 3/5y= | | -16(2.5)+13= | | 23=8n-5+6+3n | | 1/5-8/15 |

Equations solver categories